Electrical performance of conducting polymer (SPAN) grown on GaAs with different substrate orientations - Jameel, D.A.; Aziz, M.; Felix, J.F.; Al Saqri, N.; Taylor, D.; Albalawi, H.; Alghamdi, H.; Al Mashary, F.; Henini, M. (Elsevier, 2016)
This article reports the effect of n-type GaAs substrate orientation, namely (100), (311)A and (311)B, on the electrical properties of sulfonated polyaniline (SPAN)/GaAs heterojunction devices. In addition, the inhomogeneity of the interface between various GaAs substrates and SPAN is investigated in terms of barrier height and ideality factor by performing I–V measurements at different temperatures (20–420K). The I–V results indicate that the value of the rectification ratio (IF/IR) at 0.5V is higher for SPAN/(311)B GaAs samples than for SPAN/(100) GaAs and SPAN/(311)A GaAs samples. Moreover, the barrier height decreases and the ideality factor increases with decreasing temperature for all three heterostructure devices. The high value of mean barrier ˚¯ b of SPAN/(311)B (calculated from the plots of ˚b0 as a function of 1/2kT) confirms that the GaAs substrate orientation results in an increase of barrier homogeneities. Furthermore,the C-V characteristics were obtained at room temperature. The C-V measurements showed that the carrier distributions at the interface and away from the interface in high index (311) GaAs orientations are more uniform and have better barrier homogeneity than those grown on the conventional (100) GaAs substrates.